INDONESIAN NATURAL ZEOLITES MARKETING - Apandi, Toni Toha (Jurnal Zeolit Indonesia, 2002)
Natural zeolites have been known and studied in Indonesia since the 1980s. In 1986, a pilot processing plant for natural zeolites was built in Bayah, Lebak regency where some applied research was performed. This was with cooperation with the universities, research and development centres, technical institutions and others. By their cooperation, and informal recommendations relating to Indonesian zeolite deposits, the joint work has created a focus of applied research in a market segment which has the great possibility to be a captive market. It started from the fields of aquaculture of schrimp ponds, water treatment of drinking and sewage water, and agriculture. Beginning with the difficulty of getting a phosphate fertilizer, there is a booming of domestic natural zeolite demand in agriculture; even natural zeolites exports are also gradually increasing by means of international zeolites market growth and globalisation of information systems. Indonesia has great natural zeolites deposits and has attracted much attention from foreign entrepreneurs to invest in the zeolites business especially in the production of high quality zeolites. However, it is necessary to socialize and convince all of the potential association to join organizations in order to get more synergism between the members in chambers of commerce and industry (KADIN) as a facilitator, for example to facilitate a company association and a professional association such as Indonesian Zeolite Association (IZI) to coordinate their programme and planning.